REAKSI FORMASI PADA KARAKTER BRUCE WAYNE DALAM SERI FILM BATMAN - Yanuar Ramadhan; Tatan Tawami (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2021)
The purpose of this research is to explain the reaction mechanism of the formation released by Bruce Wayne's character to dampen impulses from the id structure. Reaction formation is a type of ego defense mechanism that seeks to lessen the anxiety impulse that is created by the id’ structure, which causes actions that are not in line with what the individual wishes to do or feel. This research technique examines Bruce Wayne's protection mechanisms in the film Batman Begins using qualitative approaches in a descriptive style (2005). According to research, Bruce Wayne's character uses reaction formation to defend others. To overcome the challenges he faced, Bruce's paradigm of his job as protector of the city of Gotham forced him to deploy formation reflexes. The findings of this study are expected to be used as a model for other researchers exploring the formation reaction defense mechanism in greater depth. Keywords: Formation reaction, Defense Mechanism, Bruce Wayne.